2006
DOI: 10.1007/s12094-006-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hemoglobin levels on survival after radical treatment of esophageal carcinoma with radiotherapy

Abstract: As found for other solid tumors, hemoglobin level was a determining factor in the prognosis for treatment outcome in patients with esophageal carcinoma. Our findings require confirmation in randomized studies and further documentation of the probable benefits of correcting hemoglobin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…We found that symptoms, performance status, and use of analgesics seemed to better prognosticate survival than the tumor characteristics. The reduced performance status and higher level of weight loss at admission in the ‘short’ survivors, compared to the ‘long’ survivors, is similar to data reported in other studies 2–4 . The associations found between levels of pain and swallowing difficulties on the one hand and survival on the other are not commonly reported.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found that symptoms, performance status, and use of analgesics seemed to better prognosticate survival than the tumor characteristics. The reduced performance status and higher level of weight loss at admission in the ‘short’ survivors, compared to the ‘long’ survivors, is similar to data reported in other studies 2–4 . The associations found between levels of pain and swallowing difficulties on the one hand and survival on the other are not commonly reported.…”
Section: Discussionsupporting
confidence: 87%
“…It is important to choose a treatment modality that rapidly relieves the dysphagia, preferably with a short hospital stay. In addition, the duration of the response should be adequately relative to the patients' life expectancy which has been reported to be related to clinical prognostic factors such as performance status, weigh loss, tumor length, clinical stage, 2–4 but also to sex and age 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each unit increase the risk of death decreased by 5%. 10 An investigation of 124 patients treated with radiotherapy or chemoradiotherapy (CRT) for oesophageal cancer found that pre-treatment I Tanswell, H Steed, S Ahmad, J Butterworth, G Townson clinical haemoglobin levels of 12.1-14g/dl were associated with the best overall survival, followed by >14 g/dl and then <12 g/dl (p<0.001). 11 A retrospective investigation of prognostic value of haemoglobin during radiochemotherapy of 108 patients found that haemoglobin levels of greater than 12 g/dl was associated with significantly increased overall survival rates (p=0.002).…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14,16 However most studies are small, many focus on the SCC subtype and a meta-analysis is required to review and clarify the use of haemoglobin as a prognostic factor pre-treatment and during treatment. This analysis fails to demonstrate an association between baseline anaemia and reduced overall survival in the SCC subtype, which supports the findings of Hofheink et al 15 One small study of 56 patients given combined CRT for unresectable oesophageal cancer found 30% of these patients were given blood transfusions during CRT.…”
mentioning
confidence: 99%